A new instrument to promote knowledge-led growth: the Global Liveable Cities Index. (1st January 2014) - Tan, Khee Giap; Woo, Wing Thye; Tan, Boon Seng
At a time of increasing mobility of talent, attracting human capital has become the critical success factor to fuel knowledge-led growth. This paper uses the notion of 'liveability' to denote the broader set of criteria to attract such talent and measures these criteria with the Global Liveable Cities Index (GLCI) which encompasses 85 indicators. We constructed the eclectic GLCI, which combines both aspects, for 64 global cities and conducted a policy simulation where each city improved its weakest 20% indicators to average levels. The simulation showed dramatic improvement to the city's liveability and is a useful tool for policymakers to improve the city's competitiveness.